The effect of cyanobacterial compounds on the organogenesis of pea cultured in vitro - Molnár, Zoltán; Ördög, Vince (Acta Biologica Szegediensis, 2005)
Many experimental results suggest the plant growth regulator (PGR) content and its physiological function in macro- and microscopic algae. Various compounds of cyanobacteria could be useful sources to enhance or substitute the influence of synthetic PGRs on tissue cultures of recalcitrant plants in vitro. In this study we have evaluated the beneficial effects of some extracellular compounds derived from axenic cultures of cyanobacteria. The cyanobacterial compounds in biomass alone have produced lower rates of shoot regeneration and gained smaller fresh weights compared to the PGRs control. They are not like real substitutes of synthetic PGRs but as a supplement in culture media resulting more vigorious cultures and regenerated shoots.